Patterns of Infraorbital Nerve Injury in Zygomatic Maxillary Complex Fractures: A Study from A Public Hospital in Karachi: Patterns of Infraorbital Nerve Injury in Zygomatic Maxillary Complex Fractures - Saleem, Qasim; Shaikh, Tanzeela; Akhtar, Zulakha; Samreena, .; Habiba, Ume; Irshad, Farah (Pakistan Journal of Health Sciences, 2024)
The zygomatic region is highly susceptible to zygomatic maxillary Complex fractures, making it the second most common facial fracture in the lateral midface. Objective: To determine the types and frequencies of infraorbital nerve injuries (anesthesia, paresthesia, dysesthesia, and hypoesthesia) in patients with zygomatic maxillary complex fractures. Methods: A cross-sectional study was conducted over six months at the Department of Oral and Maxillofacial Surgery, Jinnah Postgraduate Medical Centre, Karachi. The total sample size of 72 was determined using OPEN-EPI software, based on a 95% confidence interval, 7% margin of error, and an assumed 89.77% proportion of infraorbital nerve injury in zygomatic maxillary fractures from a previous study. Non-probability consecutive sampling was employed. Demographic data (gender, age, residence, Body Mass Index) and infraorbital nerve injuries were recorded, and categorized into hypoesthesia, paresthesia, dysesthesia, and anesthesia based on clinical examination and radiographs. Data were analyzed using SPSS version 20.0, with means and percentages used for analysis. The chi-square test was utilized to explore associations between categorical variables. Results: Among 72 patients, 62.5% were male, with a mean age of 37.43 ± 11.04 years. Urban residents made up 65.3%. The mean Body Mass Index was 24.77 ± 3.0 kg/m², and 19.4% were obese. Infraorbital nerve injury was present in 75% of cases, with paresthesia the most common (59.7%), followed by hypoesthesia (8.3%), dysesthesia (4.2%), and anesthesia (2.8%). Conclusion: It was concluded that infraorbital nerve injuries are frequent in zygomatic maxillary fractures, with paresthesia being the most common. Early detection and treatment are essential to improve patient outcomes.